Bringing the social into the accounting curriculum : integrating a sociological approach into learning and teaching in accounting : final report. - Boyce, Gordon; Greer, Susan; Narayanan, Venkateshwaran; Blair, Bill (Australia, Dept of Education and Training, 2017)
The role of accounting in the financial and economic controversies of recent times highlights an urgent need for educative reform, specifically to address the social and ethical relevance of accounting curriculum. This is the final report from a project focused on curriculum renewal in Australian higher education. The approach to curriculum renewal adopted in this project was centred on an aspiration to 'teach to the future', looking beyond the limitations of traditional narrow disciplinary boundaries to improve the quality of accounting education. This was achieved by drawing on critical- sociological concepts to support the development of a curriculum that integrates critical reflection and transformative learning and teaching. The distinctive approach in this project involved the use of research activities (content and critical analysis, interviews, focus groups) to develop a scaffolded framework for the integration of sociological concepts and analytical approaches into the accounting curriculum, with reference to, and relevance for, International Accounting Education Standards.